Fine‐scale hydrological niche differentiation through the lens of multi‐species co‐occurrence models. (15th June 2015) - Letten, Andrew D.; Keith, David A.; Tozer, Mark G.; Hui, Francis K.C.; Fridley, Jason
<x xml:space="preserve">Abstract</x> This study conrms the vital role of hydrological niches for the maintenance of within‐community plant diversity, but also highlights the need for more rigorous analysis of scale dependencies to better understand the underlying coexistence mechanisms at play. In addition, it illustrates the inferential gains madepossible with model‐based approaches to the analysis of species co‐occurrence. R code illustrating model fitting and inference is provided as a supplement. <boxed-text content-type="graphic" id="jec12428-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>